2009
DOI: 10.1074/jbc.m109.001032
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HARMLESS TO OZONE LAYER Protein Methylates a Glucosinolate Breakdown Product and Functions in Resistance to Pseudomonas syringae pv. maculicola

Abstract: Almost all of the chlorine-containing gas emitted from natural sources is methyl chloride (CH 3 Cl), which contributes to the destruction of the stratospheric ozone layer. Methyl chloride (CH 3 Cl) is the most abundant halohydrocarbon emitted into the atmosphere and constitutes about 17% of the chlorine currently in the stratosphere (1). CH 3 Cl is derived mainly from natural sources and contributes to the destruction of the stratospheric ozone layer. As the total abundance of ozone-depleting gases such as chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…hol1 seedlings are more susceptible to infection by P. syringae pv. maculicola (Nagatoshi and Nakamura, ). Isoflavone‐ O ‐methyltransferase (IOMT) is also a SAM‐MT transferring a methyl group from SAM to isoflavones, yielding the methyl ether derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…hol1 seedlings are more susceptible to infection by P. syringae pv. maculicola (Nagatoshi and Nakamura, ). Isoflavone‐ O ‐methyltransferase (IOMT) is also a SAM‐MT transferring a methyl group from SAM to isoflavones, yielding the methyl ether derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…All kinetic analyses of plant HOL family proteins reported to date have been performed using proteins from Brassicales plants. A physiological substrate of AtHOL1 protein was suggested to be a thiocyanate ion produced by the catabolism of indole glucosinolates, which are characteristic secondary metabolites among Brassicales plants (Midorikawa et al 2009;Nagatoshi and Nakamura 2009). ese results suggested that Brassicales plants have HOL proteins that play a physiological role speci c to Brassicales plants.…”
mentioning
confidence: 81%
“…In Brassica species, glucosinolates are an important class of stress-related compounds. A mutant deficient in Harmless to Ozone Layer1 (HOL1), so called because it has only low emissions of ozone-damaging methyl halides, shows decreased resistance to bacteria, associated with compromised ability to methylate glucosinolate breakdown products (Nagatoshi and Nakamura, 2009). Together with the glucosinolate-cleaving enzyme (myrosinase) and SA-linked PR proteins (PR2, PR5), HOL1 showed increased phosphopeptide signals in cat2 and other mutants that show constitutive redox perturbation and increased resistance to pathogens (Trotta et al, 2011;Li et al, 2014).…”
Section: Other Pathwaysmentioning
confidence: 99%